INVESTIGAÇÃO DA CONTAMINAÇÃO POR METAIS EM AMBIENTES AQUÁTICOS DA CIDADE DE MACAPÁ, ESTADO DO AMAPÁ, BRASIL. - SOUZA, Debora Cristina Damasceno; VIANA, Lucilene Finoto; SILVA, Jadna Costa; MACHADO, Raquellyne Baia; CARDOSO, Claudia Andrea Lima; FLORENTINO, Alexandro Cezar (ANAIS DO ENIC, 2020)
-